PELATIHAN PENGUASAAN MENGETIK CEPAT 10 JARI DENGAN METODE DRILL DI SMK NEGERI 5 BANDAR LAMPUNG - Suripto Suripto; Supriyanto Supriyanto; Eri Maryani (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this service is to improve mastery skills and skills in fast typing for students of SMKN 5 Bandar Lampung. For the problems faced by students, namely how to apply fast typing using the drill method in order to complete work related to typing, which can be completed quickly, correctly and on time. The long-term target to be achieved in this activity is closely related to the problem of using the drill method using the typing test application which covers a very wide range for students, teachers and secretaries which leads to improving their performance. The steps taken to master fast typing are through coaching and improving fast typing exercises by using several typing test applications using the drill method. The output of this activity is the scientific article Shinta 4 Lancang Kuning University, activity videos, and service profiles published at the University of Lampung dedication seminar. The methods used are interesting discussions, lectures and practicals, about the drill method in the typing test. By holding fast typing training with the Drill method, it is intended for students of SMKN 5 Bandar Lampung, to be able to further improve their mastery and skills in fast typing.